How do individuals cope during post-conflict recovery? Evidence from post-war Northern Uganda - Carlos Bozzoli; Tilman Brück; Tony Muhumuza (Weekly Report, 2011)
Despite the widespread prevalence of violent conflict in most destitute regions of the world, little is known about the realities of individuals affected and the difficult decisions they have to take. In this report we address this issue by providing an insight into how individuals cope during post-conflict recovery in Northern Uganda. We particularly compare individuals who still reside in displacement camps with those that have already reintegrated into their original communities. Our focus is on opportunities and constraints they encounter during recovery with regard to employment choices. Individuals who reside in camps may be more inclined to engage in certain welfare-enhancing activities than their counterparts who chose to reintegrate. Results highlight the possibility of displaced individuals possessing productive skills that may be relevant for recovery.
Keywords: J01; J60; O12; 330; conflict; IDP; Northern Uganda